A new approach to estimating private returns to R&D - Ådne Cappelen; Pierre A. Mohnen; Arvid Raknerud; Marina Rybalka (Statistics Norway, Research Department, 2023)
This paper revisits the estimation of private returns to R&D. In an extension of the standard approach, we allow for endogeneity of production decisions, heterogeneity of R&D elasticities, and asymmetric treatment of intramural and extramural R&D. Our empirical analyses are based on an extended Cobb-Douglas production function that allows for firms with zero R&D capital, which is especially useful for studying firms' transition from being R&D-non-active to becoming R&D-active. Using a large panel of Norwegian firms observed in the period 2001-2018, we estimate the average private net return to be in the range 0-5 percent across a variety of model specifications if we treat intra- and extramural R&D symmetrically. If in compliance with the Frascati manual, we treat intramural R&D as investment and extramural R&D as intermediate input, the estimated net return increases to 5-10 percent.
Keywords: C33; C52; D24; O38; 330; Returns to R&D; Intramural R&D; Extramural R&D; Capitalization of R&D; Dynamic panel data models; GMM